Deficiency in platelet 12-lipoxygenase exacerbates inflammation and disease severity during SARS-CoV-2 infection - Ana Claudia dos S. P. Andrade; Emile Lacasse; Isabelle Dubuc; Leslie Gudimard; Annie Gravel; Florian Puhm; Gabriel Campolina-Silva; Celso Queiroz-Junior; Isabelle Allaeys; Julien Prunier; Oumaima Azeggouar Wallen; Élizabeth Dumais; et al. (Proceedings of the National Academy of Sciences, 2025)
Platelets, known for maintaining blood balance, also participate in antimicrobial defense. Upon severeacute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, platelets become hyperactivated, releasing molecules such as cytokines, granule contents, and bioactive lipids. The key effector biolipids produced by platelets include 12-hydroxyeicosatetraenoic acid (12-HETE) and 12-hydroxyeicosatrienoic acid (12-HETrE), produced by 12-lipoxygenase (12-LOX), and prostaglandins and thromboxane, produced by cyclooxygenase-1. While prostaglandin E2 and thromboxane B2 were previously associated with lung inflammation in severe COVID-19, the role of platelet 12-LOX in SARS-CoV-2 infection remains unclear. Using mice deficient for platelets’ 12-LOX, we report that SARS-CoV-2 infection resulted in higher lung inflammation characterized by histopathological tissue analysis, increased leukocyte infiltrates, and cytokine production relative to wild-type mice. In addition, distinct platelet and lung transcriptomic changes, including alterations in NOD-like receptor (NLR) family pyrin domain-containing 1 (NLRP1) inflammasome-related gene expression, were observed. Mass spectrometry lipidomic analysis in 12-LOX-deficient-infected mice revealed significant changes in bioactive lipid content, including reduced levels of 12-HETrE that inversely correlated with disease severity. Finally, platelet 12-LOX deficiency was associated with increased morbidity and lower survival rates relative to wild type (WT) mice. Overall, this study highlights the complex interplay between 12-LOX-related lipid metabolism and inflammatory responses during SARS-CoV-2 infection. The findings provide valuable insights into potential therapeutic targets aimed at mitigating severe outcomes, emphasizing the pivotal role of platelet enzymes in the host response to viral infections.